Modeling Symptoms of Dyslexia Based on Working Memory and Anxiety with the Mediating Role of Information Processing Speed in Children - Khazanedarloo, Ladan; Ahmadi, Reza; Ghazanfari, Ahmad (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to predict symptoms of dyslexia based on working memory and anxiety, with the mediating role of information processing speed in children.Materials and Methods: The research method was correlational with a path analysis design. The statistical population included all male and female students in the fourth to sixth grades during the 2023–2024 academic year in Tehran, from which 300 students were selected using purposive sampling. The research instruments included the Reading and Dyslexia Test (NEMA; Karami Noori & Moradi, 2005), the Dyslexia Checklist (RLDT; Azizzian & Abedi, 2003), the Wechsler Intelligence Scale for Children – Fourth Edition (WISC-IV), and the Short Form of the Spence Children’s Anxiety Scale (SCAS; Ahlen et al., 2018).Findings: The results of path analysis indicated that the direct effect of working memory on dyslexia symptoms was significant (p < .05). The direct effect of anxiety on dyslexia symptoms was also significant (p < .05). Furthermore, the direct effect of information processing speed on dyslexia symptoms was significant (p < .05). The direct effect of working memory on information processing speed was significant (p < .05), and the direct effect of anxiety on information processing speed was also significant (p < .05). Additionally, the indirect effect of working memory on dyslexia symptoms through the mediating role of information processing speed was significant (p < .05), and the indirect effect of anxiety on dyslexia symptoms through the mediating role of information processing speed was also significant (p < .05).Conclusion: Based on the obtained results, implementing interventions aimed at improving working memory and reducing anxiety may help decrease symptoms of dyslexia in children.